242. ENDOSCOPIC MUCOSAL CONGESTIVE CHANGE ON POSTOPERATIVE DAY 1 AS A PREDICTIVE FACTOR OF POSTOPERATIVE ANASTOMOTIC STRICTURE. (24th September 2022) - Fujiwara, Naoto; Ito, Sono; Shigeno, Takashi; Kakuta, Ryota; Shinohara, Hajime; Shiobara, Hiroyuki; Saito, Katsumasa; Hoshino, Akihiro; Okada, Takuya; Kawada, Kenro; Tokunaga, Masanori; Kinugasa, Yusuke
Abstract: Anastomotic stricture is one of the crucial complications after the esophageal cancer surgery. Although anastomotic leakage is said to be a risk factor, anastomotic stricture can also occur without anastomotic leakage. From 2008, we have routinely conducted endoscopy on postoperative day 1, and evaluated the anastomotic site or mucosal condition of reconstructed organ. Among these data, we focused on the mucosal congestive change and examined the association with postoperative anastomotic stricture. From 2010 to 2015, 203 esophageal cancer patients were conducted esophagectomy with retrosternal gastric tube reconstruction in Tokyo Medical and Dental University. Among them, 197 patients for which endoscopic data on postoperative day 1 were obtained were included in this study. Mucosal congestion was defined as blue or black color on endoscopic findings, and classified into four groups as absent, mild, moderate, and severe. Univariate and multivariate analysis were performed to clarify the relationship between the mucosal congestive change on endoscopic findings and occurrence of postoperative anastomotic stricture. Among 197 patients, 60 patients (30.4%) experienced postoperative anastomotic stricture. Univariate and multivariate analysis revealed that the mucosal congestive change as moderate or severe was the independent risk factor for postoperative anastomotic stricture along with lower pathological Stage. Circular stapler size used for esophago-gastric anastomosis or postoperative anastomotic leakage were not independent risk factors for postoperative anastomotic stricture in this study. It is said that congestive change induces secondary ischemia because of the high internal tissue pressure, and sometimes causes more severe damage than arterial ischemia. Our postoperative endoscopic evaluation method is useful to detect the risk of developing anastomotic stricture in early postoperative state. In such cases, management of postoperative fluid balance might be important to prevent postoperative anastomotic stricture, but it requires further investigation.